Constitution - Main Law? - Artemii E. Guzii (Сибирское юридическое обозрение)
The Author discusses the legal nature of the Russian Constitution. A dialectical analysis is made of the concept of “main law” in the current doctrine of constitutional law, based on which concludes that there is no single approach to the nature of the object. During the general theoretical analysis of the legal system of the Russian Federation, the Author identifies a number of criteria, which differ the concept of a constitution from the concepts of "law" and " sub-legislative act". Based on the above, a conclusion is made about the imperfection of theoretical understanding of the legal nature of the constitution in modern Russia, an alternative definition of this concept and its place in the system of Russian legislation is given.